Capital Controls and Financial Crisis Management Lessons From the 1990s and 2000s - Pierre-jacques, Ralph (Université d'Ottawa | University of Ottawa, 2011)
There are ongoing discussions surrounding the re-imposition of capital account restriction in the context of emerging market economies (EMEs). These discussions have arisen primarily as a result of the recent global financial crisis, and the subsequent dy